Expanding functional repertoires of fungal peroxisomes: contribution to growth and survival processes - MARUYAMA, Jun-ichi; KITAMOTO, Katsuhiko (Frontiers in Physiology, 2013)
It has long been regarded that the primary function of fungal peroxisomes is limited to the β-oxidation of fatty acids, as mutants lacking peroxisomal function fail to grow in minimal medium containing fatty acids as the sole carbon source. However, studies in filamentous fungi have revealed that peroxisomes have diverse functional repertoires. This review describes the essential roles of peroxisomes in the growth and survival processes of filamentous fungi. One such survival mechanism involves the Woronin body, a Pezizomycotina-specific organelle that plugs the septal pore upon hyphal lysis to prevent excessive cytoplasmic loss. A number of reports have demonstrated that Woronin bodies are derived from peroxisomes. Specifically, the Woronin body protein Hex1 is targeted to peroxisomes by peroxisomal targeting sequence 1 (PTS1) and forms a self-assembled structure that buds from peroxisomes to form the Woronin body. Peroxisomal deficiency reduces the ability of filamentous fungi to prevent excessive cytoplasmic loss upon hyphal lysis, indicating that peroxisomes contribute to the survival of these multicellular organisms. Peroxisomes were also recently found to play a vital role in the biosynthesis of biotin, which is an essential cofactor for various carboxylation and decarboxylation reactions. In biotin-prototrophic fungi, peroxisome-deficient mutants exhibit growth defects when grown on glucose as a carbon source due to biotin auxotrophy. The biotin biosynthetic enzyme BioF (7-keto-8-aminopelargonic acid synthase) contains a PTS1 motif that is required for both peroxisomal targeting and biotin biosynthesis. In plants, the BioF protein contains a conserved PTS1 motif and is also localized in peroxisomes. These findings indicate that the involvement of peroxisomes in biotin biosynthesis is evolutionarily conserved between fungi and plants, and that peroxisomes play a key role in fungal growth.